MG-134 Validation of a customizable next generation sequencing panel for ear and eye diseases. (4th December 2015) - Cody, Neal; Delio, Maria; Wang, Jinlian; Vij, Geetu; Cai, Guiqing; Webb, Brynn; Yang, Amy; Kasai, Yumi; Sperber, Steven; Kornreich, Ruth; Edelmann, Lisa
Abstract : Background: Hearing and/or vision loss can result from both genetic and non-genetic etiologies. Up to 70% of prelingual hearing loss has a genetic basis, as does up to 60% of congenital blindness among infants. Next generation sequencing (NGS) technology is ideal for diagnostic testing for such disorders due to extreme locus heterogeneity and phenotypic overlap. Objectives: The aim is to design and validate a comprehensive, customizable NGS panel for detection of pathogenic variants in genes involved in hearing and/or vision loss. Design/method: 380 genes were selected for inclusion based on literature review and comparison with commercially available assays, including 245 genes for vision loss and 83 genes for hearing loss. Agilent SureSelect biotinylated RNA baits were designed to capture 1.5 Mb of DNA using SureSelect XT target enrichment followed by Illumina HiSeq 2500 sequencing. DNA from six HapMap cell lines and five Coriell repository samples with known pathogenic variants were used to assess intra-run and inter-run variability. Additionally, DNA from a family with a known hearing loss aetiology was included. Results: An average yield of 6 Gb of sequence per sample was obtained, where 94% of bases were covered at a depth >20X. Genotype calls from HapMap samples were highly concordant across three runs. Eight known pathogenic variants were confirmed in GJB2, USH1C, MARVELD2, TRIOBP, and OAT. Conclusions: This NGS panel targets an extensive list of genes implicated in diseases of the ear and the eye. Customizable testing allows ordering of an ear-specific or eye-specific gene panel, or both.